Contemporary art: cultivating Feng Zikai’s teachings - Jiangyang Xie; Xiaomin Chen (Trans/Form/Ação)
In response to the current lack of innovative and aesthetic abilities in art, this article deeply explored Feng Zikai’s art thought and its contemporary value. As a great artist with multiple identities, Feng Zikai’s artistic ideas are not only a valuable asset in the field of art, but also of great significance in promoting the development of contemporary art. This article elaborated on Feng Zikai’s art thoughts, principles and education theories, and on the contemporary value of his art thoughts, from four perspectives: humanistic care, cultural innovation, service level and social harmony. Through research, it has been found that Feng Zikai’s art thoughts are deeply humanistic, compatible and sustainable, with the ancient as the new and improving service levels, with the people as the foundation. Qu Gao’s and the masses’ thoughts play an important role in shaping children’s personality and character, enhancing aesthetic and cultural innovation abilities, and also have certain guiding significance for today’s socialism. This article hoped to provide more reliable experience and theoretical basis for the cultivation and development of art through the study of Feng Zikai’s art thoughts and the times’ value.